Work unit context: The dyadic, team members relationships and group outcomes in a Malaysian organization - Ismail, Nur Qurratul' Aini; Hamzah, Mohd Hilmi; Ngah, Kamarudin; Mustaffa, Jamaludin; Zakaria, Zaherawati; Noordin, Nazni (Society for Business Management Dynamics, 2012)
This article proposed a group behavior model based on group size, dyad and team-member relationship exchange quality.The objective of this study is to identify the relationship between the size of the working group, leader-member exchange quality, team-member exchange quality that impact on the work group affective commitment as a group outcomes.A total of 215 employees (n=215) in the organization involved in plantation industry throughout Malaysia, was taken as the sample. Data were analyzed using multiple regression to examine the relationship between variables, namely, leader member exchange quality, team-member exchange quality and affective commitment.While the Pearson correlation analysis was used to test the work group size, team-member exchange quality and leader-member exchange quality. The main finding by pearson correlation analysis revealed a negative relationship between workgroup size and leader-member exchange quality and team-member exchange quality. This means that the larger of workgroup size, leader-member exchange and team-member exchange quality was decreasing. The results of the multiple regression analysis showed a significant positive correlation between leader-member exchange and team-member exchange quality of the affective commitment of the workgroup. Based on these findings, several suggestions were put forward as a business and approach to enhance and sustain commitment in workgroups and networking among member groups and their leaders are directly able to improve organizational performance.